FAMILY HAPPINESS, SOCIOECONOMICS, AND SOCIODEMOGRAPHY: FACTS IN INDONESIA - Alwi, Ahmad Chafid; Mulyani, Endang (Universitas Negeri Yogyakarta, 2022)
Socioeconomics and sociodemography these days are often used as a measure of people's happiness in a country. This study took data from the World Values Survey from Indonesia, with 3200 participans from various work backgrounds, ages, etc. This research uses explanative design. A quantitative approach and type of analyzes use the probit method to see the modeling of happiness, socio-economic and socio-demographic variables. The results showed that age and gender are not determinants of happiness. It appears that the happiness of the Indonesian people is still primarily determined by their income. Low, medium, and high job class variables have a significant influence. Furthermore, marital status, which is described by the existence of marriage, living together like married, divorced, separated, widowed/widowed, and unmarried, influences the happiness variable of family living standards. Still, the exciting thing is that Indonesian society is more likely to have a high standard of living, not to be a determinant of happiness. Indonesia's high standard of living looks different from some research in other countries and previous research that can be a determinant of happiness. These facts certainly impact government policy considerations in realizing public welfare, as stated in the foundation of the state ideology of Pancasila.